Descartes : an intellectual biography - Gaukroger, Stephen (Oxford University Press, 1995)
The results of Descartes' work in mathematics and science are still of benefit to science today. This book shows how he developed his ideas and how his work informed the later studies in philosophy for which he is renowned.